STRATEGI PEMASARAN, PERKEMBANGAN PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PEMEBELIAN SPAREPART DI TOKO DNA DWI ABADI MUARA TEWEH - Sofia SOFIA; Riska Amelia Tri Ananda (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2025)
This study aims to analyze how marketing strategies, product development, and service quality influence customer satisfaction in purchasing spare parts at the DNA DWI Abadi Muara Teweh Store. With increasingly fierce competition in the automotive industry, spare parts stores need to implement appropriate marketing strategies, tailor products to buyer needs, and provide good service to maintain customer loyalty. The method used in this study is quantitative, by distributing questionnaires to 50 customers of the DNA DWI Abadi Store. The collected data were then tested for validity and reliability, then further analyzed using correlation and regression methods to determine the effect of the independent variables (marketing strategy, product development, and service quality) on the dependent variable (customer satisfaction). The results of the study indicate that all three variables have a significant influence on customer satisfaction. Among the three, service quality is the most influential factor, where aspects such as staff friendliness, timeliness of service, and availability of products according to needs greatly influence customer loyalty.